Method for preparing acesulfamide lithium
The preparation of acetysulfonate is solved by a multi-step method including preparation of acetoacetylsulfonate, hydrolysis and extraction, reaction and pH adjustment of lithium hydroxide, use of adsorbent materials, concentration and crystallization, and washing and drying. The problem of high potassium ions and difficulty in controlling raw material purity in the lithium process has achieved the preparation of lithium acesulfame crystals with high purity and low impurity content.
Patent Information
- Application Number
- CN202411787274.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
AI Technical Summary
In the preparation of lithium acesulfame, there is a problem of high potassium ions in the prior art, and it is difficult to control the purity of the raw material and the reaction conditions, which affects the purity and performance of the final product.
A multi-step method is adopted, including the preparation of acetoacetylsulfonate, the preparation of sulfur trioxide/dichloromethane solution, hydrolysis and extraction, reaction of lithium hydroxide and pH adjustment, and the use of chitosan sulfate adsorption materials Remove sulfate ions, concentrate and crystallize, and wash and dry to ensure control accuracy and purity requirements for each step.
The high purity and low impurity content of lithium acesulfame crystals are achieved, and the performance and quality of the product are improved.
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing a chemical raw material, and in particular to a method for preparing lithium acesulfame. Background Art
[0002] The mechanism of acesulfame as a battery additive mainly involves the chemical and electrochemical reactions it forms in the battery electrolyte.
[0003] As an electrolyte salt, lithium acetylsulfamate has important application prospects in lithium-ion battery electrolytes. However, the process of converting lithium acetylsulfamate through potassium acetylsulfamate has the problem of high potassium ions.
[0004] The preparation of lithium acesulfame requires the control of specific reaction conditions, such as temperature, pressure and reaction time. Slight changes in these conditions may have a significant impact on the purity and performance of the final product. The purity of the raw materials has an important impact on the purity and performance of the final product. Therefore, when preparing lithium acesulfame, it is necessary to ensure that the raw materials used have high purity. Some waste or pollutants may be generated during the preparation and use of lithium acesulfame. These waste or pollutants may have a certain impact on the environment.
[0005] As an electrolyte salt, lithium acesulfame has important application prospects in lithium-ion battery electrolytes. The process of converting lithium acesulfame through potassium acesulfame may involve complex chemical synthesis steps and environmental factors. Potassium ions, as part of the electrolyte salt, need to be removed during the preparation process. If they are not removed, the performance of the electrolyte may be affected to a certain extent.
[0006] Chinese patent document CN116322984A discloses a method for preparing acesulfame potassium. The method includes five main steps: first, aminosulfonic acid and amine are mixed to react to obtain aminosulfonic acid amine salt; secondly, aminosulfonic acid amine salt is reacted with diketene to obtain a first material; then, the first material is reacted with sulfur trioxide solution to obtain a second material; then, the second material is reacted with a hydrolyzate to obtain a third material; finally, the organic phase separated from the third material is reacted with a potassium-containing compound to obtain acesulfame potassium. It is worth noting that the patent emphasizes in step 3 that acetoacetyl-N-sulfanilic acid amine salt and sulfur trioxide are continuously reacted at a constant amount ratio of substance, thereby ensuring the continuity and stability of the reaction. Patent document CN116323573A focuses on the method for preparing acesulfame acid by hydrolysis, and further relates to a production method for acesulfame potassium. The method comprises four key steps: first, aminosulfonic acid and triethylamine are mixed to react to obtain aminosulfonic acid triethylamine salt; second, aminosulfonic acid triethylamine salt is reacted with diketene to obtain acetoacetylsulfanilic acid triethylamine salt; then, acetoacetylsulfanilic acid triethylamine salt is reacted with sulfur trioxide to obtain a first material; and finally, the first material is reacted with a hydrolyzing agent (aqueous sulfuric acid solution) to obtain a second material.
[0007] For lithium acesulfame, the above method can certainly be used for preparation, but there are also some new problems. Summary of the invention
[0008] The present invention provides a method for preparing lithium acesulfame, comprising the following steps:
[0009] (a) preparing acetoacetamidosulfonate;
[0010] (b) preparing a sulfur trioxide / dichloromethane solution;
[0011] (c) preparing an intermediate using the products of steps (a) and (b);
[0012] (d) hydrolyzing and extracting the intermediate to obtain an organic phase containing acesulfame;
[0013] (e) adding lithium hydroxide to deionized water, adjusting the pH value to 6.5-7, and then reacting with the organic phase containing acesulfame;
[0014] (f) using chitosan-based sulfate adsorbent to remove sulfate ions from the reaction solution;
[0015] (g) filtering to remove the adsorbent material, concentrating and crystallizing to obtain a crude product of lithium acesulfame;
[0016] (h) washing and drying the crude lithium acesulfame.
[0017] In step (e), the pH value of the mixed solution is adjusted by adding sulfuric acid.
[0018] In step (e), the lithium ion concentration of the lithium hydroxide solution is 3-4 mol / L.
[0019] In step (f), the chitosan-based sulfate adsorption material is prepared by a cross-linking reaction of chitosan and formaldehyde and is protonated.
[0020] In the preparation of chitosan-based sulfate adsorption material, the deacetylation degree of chitosan is between 80% and 95%, and the particle size is between 50 and 100 microns.
[0021] In the preparation of chitosan-based sulfate adsorption material, 2%-5% acetic acid solution is used as a solvent for chitosan.
[0022] In the preparation of chitosan-based sulfate adsorption material, the mass ratio of formaldehyde to chitosan is between 1:1 and 2:1, and the temperature of the cross-linking reaction is between 50-70°C.
[0023] In step (f), the adsorption operation is carried out at a temperature of 40-50° C., and the adsorption material is slowly added at a rate of 2% per minute.
[0024] In step (g), the concentration operation is carried out under the conditions of a vacuum degree of -0.08 to -0.1 MPa and a heating temperature of 60-80°C.
[0025] In step (g), when the solution reaches saturation concentration, the crystallization operation is started, and the concentration is continued until enough crude lithium acesulfame is obtained.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] The lithium acesulfame crystals prepared by the method of the present invention have the advantages of high purity, low impurity content, etc. DETAILED DESCRIPTION
[0028] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0029] The process for preparing acesulfame potassium in the prior art is very mature. The present invention provides a method for preparing acesulfame lithium.
[0030] 1. Preparation of acetoacetamidosulfonate
[0031] Raw materials and solvents: Aminosulfonic acid, as the main reactant, should have a purity of not less than 99%, and the amount used can be adjusted according to the specific production scale, for example, 500g. Triethylamine, as a catalyst and solvent, should have a purity of more than 99%, and the amount used is about 600ml to ensure the uniformity and reaction efficiency of the reaction system. Dichloromethane, as a solvent, should have a purity of not less than 99.5%, and the amount used should be sufficient to completely dissolve the reactants and form a stable suspension.
[0032] Reaction conditions and control: The reaction is carried out at a low temperature of 0-5°C to prevent the occurrence of side reactions and decomposition of the product. Precise temperature control is achieved by circulating a constant temperature water bath or refrigerated brine. Stirring and ventilation: During the reaction, continuous stirring is maintained to ensure that the reactants are fully in contact. At the same time, diketene (e.g., 650 g) is slowly introduced, and the ventilation rate is controlled at about 5-10 g per minute to avoid local overheating and runaway reaction. Reaction time: The reaction time is usually 2-4 hours. The reaction is judged to be complete by monitoring the transparency and color change of the reaction solution. After the reaction is completed, a nearly colorless acetoacetamidosulfonate solution is obtained. Possible solid impurities are removed by vacuum filtration or centrifugation to ensure that the solution is clear and transparent.
[0033] 2. Preparation of sulfur trioxide / dichloromethane solution
[0034] Raw materials and solvents: Sulfur trioxide, as a sulfonating agent, should have a purity of more than 99%, and the dosage is about 200g. Dichloromethane, as a solvent, is used in an amount of about 1000ml to ensure that sulfur trioxide is fully dissolved and dispersed.
[0035] Reaction conditions: During the reaction, keep stirring and control the temperature between -5 and 0°C to prevent the polymerization and side reactions of sulfur trioxide. The introduction rate of sulfur trioxide should be controlled at about 5-10g per minute to ensure the smooth progress of the reaction.
[0036] Product treatment: After the reaction is completed, a sulfur trioxide / dichloromethane solution is obtained. The solution should be stored at low temperature away from light to prevent decomposition and polymerization of sulfur trioxide.
[0037] 3. Preparation of intermediates
[0038] Reaction conditions and control: Cool the acetoacetamidosulfonate solution to about -10°C to ensure the smooth progress of the subsequent reaction. Slowly add sulfur trioxide / dichloromethane solution, and control the drop rate to about 5-10 ml per minute. Keep stirring and cooling at the same time to avoid local overheating and side reactions. The reaction time is usually 1-2 hours, and the reaction is judged by monitoring the color and transparency of the reaction solution.
[0039] After the reaction is completed, an intermediate solution is obtained, which should be stored at low temperature in the dark for subsequent processing.
[0040] 4. Hydrolysis and extraction
[0041] Hydrolysis operation: slowly add the intermediate solution into an appropriate amount of deionized water, while stirring and heating, so that acetoacetamidosulfate undergoes hydrolysis reaction to generate acetosulfanilic acid and sulfuric acid. The hydrolysis temperature is controlled at room temperature (about 25°C), and the hydrolysis time is usually 1-2 hours.
[0042] Extraction operation: After the hydrolysis is completed, acesulfame is extracted with dichloromethane. During the extraction process, stirring and appropriate temperature (such as room temperature) are maintained to ensure sufficient extraction. The number of extractions can be adjusted according to actual conditions, usually 2-3 times to ensure complete extraction of acesulfame.
[0043] After the extraction is completed, the organic phase (containing acesulfame) and the aqueous phase (containing sulfuric acid) are separated. The organic phase is dried over anhydrous sodium sulfate for subsequent treatment.
[0044] For steps 1 to 4, Chinese patent publications CN116322984A and CN116323573A both provide relevant descriptions.
[0045] 5. Mixing and reaction of lithium hydroxide
[0046] Raw material selection: lithium hydroxide with a purity of more than 98% is selected as the raw material.
[0047] Mixing operation: Add lithium hydroxide into an appropriate amount of deionized water.
[0048] pH adjustment: Add a small amount of sulfuric acid to the deionized water with lithium hydroxide, stirring while adding, to adjust the pH value to neutral to weakly acidic (pH 6.5-7). Use a pH meter to monitor the pH value of the solution in real time to ensure the accuracy of the adjustment. The concentration of lithium ions is 3-4 mol / L.
[0049] Neutralization reaction: Slowly drop the pH-adjusted solution into the organic phase containing acesulfame. During the dropwise addition, maintain stirring and a suitable temperature (e.g., 35-45°C) to ensure that the reaction proceeds fully. The reaction time is controlled between 1-2 hours.
[0050] 6. Adsorption and filtration
[0051] Adsorption material selection:
[0052] Chitosan-based sulfate adsorption material is an efficient and stable adsorbent, which is mainly prepared by the cross-linking reaction of chitosan and formaldehyde. This material can effectively adsorb sulfate ions in water, mainly relying on the electrostatic attraction between the amino groups or protonated amino groups on its surface and sulfate ions. For protonated modified materials, the amino groups on its surface are protonated under acidic conditions to form positively charged -NH3+, which adsorb negatively charged sulfate ions through electrostatic action.
[0053] The preparation process of chitosan-based sulfate adsorbent material includes the following steps:
[0054] Dissolution of chitosan. Use chitosan powder with a deacetylation degree between 80% and 95%, and a particle size between 50 and 100 microns. Use 2% to 5% acetic acid solution as the solvent. Too low a concentration may result in incomplete dissolution of chitosan, while too high a concentration may increase the difficulty of subsequent treatment. The dissolution temperature is room temperature, and magnetic stirring is used at a medium speed to ensure that the chitosan powder can be evenly dispersed in the acetic acid solution to avoid excessive local concentration. Stir until the chitosan is completely dissolved, which generally takes 30 minutes to 1 hour.
[0055] Cross-linking reaction. Use a 37% formaldehyde solution. The amount of formaldehyde needs to be adjusted according to the amount of chitosan. Usually, the mass ratio of formaldehyde to chitosan is between 1:1 and 2:1. The temperature of the cross-linking reaction is generally between 50-70°C. Higher temperatures help to speed up the reaction rate, but too high a temperature may cause chitosan degradation. The pH value of the cross-linking reaction needs to be controlled within the acidic range. Generally, acetic acid solution is used as the reaction medium, and the pH value is naturally maintained in the acidic range. The time of the cross-linking reaction needs to be adjusted according to the amount of formaldehyde and the reaction temperature, generally between 1-4 hours. Too short a reaction time may result in incomplete cross-linking, while too long a reaction time may increase the formation of by-products. Stir at medium to high speed to ensure that the formaldehyde solution and the chitosan solution are fully mixed to avoid excessive or low local concentrations.
[0056] Post-treatment. After the cross-linking reaction is completed, wash the product with a large amount of distilled water or deionized water to remove unreacted formaldehyde and other impurities. The number of washings is generally not less than 3 times, until the washing liquid is neutral. The washed product is placed in an oven to dry, and the drying temperature is generally controlled between 50-60°C to avoid excessive temperature causing chitosan degradation. The drying time depends on the humidity of the product and the temperature of the oven, and generally takes 12-24 hours. The dried product is crushed to the desired particle size, generally using a ball mill or a vibration mill for crushing.
[0057] Protonation modification. Sulfuric acid is used for protonation modification. Generally, an acid solution of 0.5-2 mol / L is used. Too low a concentration may result in incomplete protonation, while too high a concentration may increase the formation of by-products. The time for protonation modification is generally between 1 and 12 hours, and the specific time depends on the concentration and temperature of the acid solution. Too short a treatment time may result in incomplete protonation, while too long a treatment time may increase the degradation of chitosan. The temperature for protonation modification is generally between room temperature and 50°C. Higher temperatures help to speed up the protonation rate, but too high a temperature may cause degradation of chitosan. After the protonation modification is completed, wash the product with distilled or deionized water until it is neutral, and then dry it to constant weight.
[0058] Adsorption operation:
[0059] The aqueous phase containing sulfate ions is filtered to remove suspended matter and impurities. The filtered aqueous phase is adjusted to an appropriate pH range (usually between 6-7). The pH adjustment has an important influence on the adsorption effect and needs to be optimized according to the specific material. The aqueous phase is heated to an appropriate adsorption temperature (40-50°C). Higher temperatures help to increase the adsorption rate and amount, but care should be taken to avoid excessively high temperatures that may cause material performance degradation.
[0060] Adsorption material. Slowly add the powdered chitosan-based sulfate adsorption material to the water phase at a rate of 2% per minute. The addition speed should not be too fast to avoid excessive local concentration leading to a decrease in adsorption effect. Keep stirring during the addition process to ensure that the adsorption material can be evenly dispersed in the water phase.
[0061] Adsorption process control. After adding the adsorbent material, continue stirring and maintain the temperature between 40-50°C. Temperature control has an important influence on the adsorption effect, and it is necessary to ensure that the temperature remains constant throughout the adsorption process. Then let it stand for 1-2 hours to allow the adsorbent material to fully adsorb sulfate ions. During the standing period, it can be observed that the adsorbent material gradually settles to the bottom, forming an obvious solid-liquid separation. During the standing period, the stirring intensity can be appropriately reduced to avoid damaging the solid-liquid separation that has been formed. However, the stirring still needs to maintain a certain intensity to prevent the material from settling too quickly and causing excessive local concentration.
[0062] Subsequent treatment. After the adsorption is completed, the adsorbent material is separated from the aqueous phase by filtration. The separated adsorbent material is treated, such as washing, drying, etc., to remove the adsorbed sulfate ions and other impurities. For materials that need to be regenerated, the adsorbent material can be washed with an alkaline solution (such as sodium hydroxide solution) to restore its adsorption performance. The regenerated material can be used again for the adsorption of sulfate ions.
[0063] Layering and filtration: After the reaction is completed, the upper layer of the reaction solution (containing unabsorbed sulfate ions and a small amount of suspended matter) is transferred to the water phase storage tank; the water phase is filtered to remove suspended matter and unsettled adsorbed materials. During the filtration process, maintain an appropriate pressure difference and filtration speed (for example, the filtration pressure is controlled between 0.2-0.25MPa) to ensure that the filtrate is clear and transparent.
[0064] 7. Concentration and crystallization
[0065] Concentration operation: The aqueous phase after filtration and removal of sulfate ions is transferred to a concentration device equipped with a vacuum system and a heating device. The vacuum system and the heating device are turned on to concentrate the solution. The vacuum degree is controlled between -0.08 and -0.1 MPa, and the heating temperature is controlled between 60-80°C. As the concentration proceeds, the solvent in the solution is gradually removed, and the concentration of lithium acesulfame gradually increases.
[0066] Crystallization operation: When the solution reaches a certain concentration (e.g., saturated concentration), lithium acesulfame begins to precipitate and form crystals. Continue to concentrate until sufficient crude lithium acesulfame is obtained. During the concentration process, it is necessary to continuously observe the state of the solution and the precipitation of crystals to ensure that high-quality lithium acesulfame is obtained.
[0067] 8. Washing and Drying
[0068] Washing operation: The obtained crude lithium acesulfame is washed to remove impurities and unreacted raw materials attached to the surface of the crystal. The washing can be carried out with deionized water or a suitable solvent, and the washing number is usually 2-3 times.
[0069] Drying operation: After washing, the lithium acesulfame crystals are dried. The drying temperature is controlled between 60-80°C, and the drying time is usually 2-4 hours. The dried lithium acesulfame crystals should be white or off-white, free of impurities and odor.
[0070] Example 1
[0071] After the preparation of the intermediate is completed and hydrolysis and extraction are carried out, lithium acesulfame is prepared.
[0072] Lithium hydroxide with a purity of more than 98% was selected as the raw material, which was put into an appropriate amount of deionized water and stirred until completely dissolved. Next, a small amount of sulfuric acid was slowly added to the lithium hydroxide solution while stirring continuously to adjust the pH value of the solution to neutral to weakly acidic (pH value 6.5-7). During this process, a pH meter was used to monitor the pH value of the solution in real time to ensure the accuracy of the adjustment. Through this step, a solution with a suitable pH value and a lithium ion concentration of 3-4 mol / L was obtained, which was ready for the subsequent neutralization reaction.
[0073] The pH-adjusted lithium ion solution was slowly added dropwise to the organic phase containing acesulfame. During the addition, continuous stirring was maintained and the temperature was controlled between 35-45°C to ensure that the reaction proceeded fully. After the addition was completed, the reaction was continued for 1-2 hours, during which the changes in the reaction solution were closely observed.
[0074] In order to remove sulfate ions from the reaction solution, chitosan-based sulfate adsorbent material was used for treatment. First, the aqueous phase containing sulfate ions was filtered to remove suspended matter and impurities. Then, the filtered aqueous phase was adjusted to a suitable pH range (between 6 and 7) and heated to 40-50°C. Next, powdered chitosan-based sulfate adsorbent material was slowly added to the aqueous phase at a rate of 2% per minute, and stirring was maintained to ensure that the adsorbent material was evenly dispersed. After adsorption was completed, the adsorbent material was separated from the aqueous phase by filtration, and the separated adsorbent material was washed and dried to remove the adsorbed sulfate ions and other impurities. Finally, the aqueous phase was filtered again to remove suspended matter and unsettled adsorbent material, and a clear and transparent filtrate was obtained.
[0075] The aqueous phase after filtration and removal of sulfate ions is transferred to a concentrator equipped with a vacuum system and a heating device. The vacuum system and the heating device are turned on to concentrate the solution. Under the conditions where the vacuum degree is controlled between -0.08 and -0.1 MPa and the heating temperature is controlled between 60-80°C, the solvent in the solution is gradually removed and the concentration of lithium acesulfame is gradually increased. When the solution reaches saturated concentration, lithium acesulfame begins to precipitate and form crystals. Continue to concentrate until enough crude lithium acesulfame is obtained.
[0076] The obtained lithium acesulfame crude product was washed to remove impurities and unreacted raw materials attached to the surface of the crystals. The washing was carried out with deionized water for 2 times. After washing, the lithium acesulfame crystals were dried. The drying temperature was controlled between 60-80°C and the drying time was 3 hours. The dried lithium acesulfame crystals were white, free of impurities and odor, and met the product quality requirements.
[0077] Comparative Example 1
[0078] Compared with Example 1, the step of adding sulfuric acid to the lithium hydroxide solution to adjust the pH value in step 5 (lithium hydroxide dissolution and reaction), and the step of removing sulfate ions using a chitosan-based sulfate adsorbent material in step 6 (adsorption and filtration) are not applicable in Comparative Example 1. After lithium hydroxide is added to deionized water, it is directly added to the organic phase containing acesulfame for neutralization reaction without any pH adjustment and sulfate ion removal. The other steps remain unchanged.
[0079] Since the sulfuric acid addition and sulfate ion adsorption steps were omitted, lithium hydroxide was not completely dissolved, and the reaction between lithium hydroxide and acesulfame acid was incomplete. Later, part of lithium hydroxide mixed with lithium acesulfame acid to form a precipitate. At the same time, the sulfate impurities in the organic item needed to be removed separately later, which affected the purity and quality of the product.
[0080] Comparative Example 2:
[0081] The molar concentration of lithium ions in step five (lithium hydroxide dissolution and reaction) was changed from 3-4 mol / L to 6-8 mol / L. The other steps remained unchanged.
[0082] After changing the molar concentration of lithium ions, after adsorbing sulfate ions to generate lithium acesulfame, lithium acesulfame quickly forms a precipitate, making it impossible to separate.
[0083] The finished lithium acesulfame products obtained in the examples and comparative examples were tested by ion chromatography (IC), which is a high performance liquid chromatography technique.
[0084] The basic principle of ion chromatography is based on the separation ability of ion exchange resin. Ion exchange resin is a polymer material with ion exchange function, which contains dissociable ion groups. When the sample solution passes through the separation column filled with ion exchange resin, the ions in the sample will exchange with the ion groups on the resin, thereby achieving ion separation.
[0085] Ion exchange resins are divided into two types: cation exchange resins and anion exchange resins. Cation exchange resins usually have a negative charge and can absorb cations in the solution; while anion exchange resins have a positive charge and can absorb anions in the solution. The separation ability of the resin depends on the number and type of its ion exchange groups.
[0086] During the separation process, the sample solution is injected into the ion chromatograph through a high-pressure pump and enters the separation column through the injection valve. In the separation column, the ions in the sample undergo an exchange reaction with the ion groups on the resin. Depending on the difference in electrostatic force or affinity between the ions and the resin groups, the retention time of the ions on the resin will vary. As the eluent flows, the ions in the sample are gradually eluted and detected by the detector in the order of charge number and size.
[0087] The detector commonly used in ion chromatography is the conductivity detector. The conductivity detector determines the concentration of ions by measuring the change in conductivity of the effluent. When ions in the sample are eluted, they cause a change in the conductivity of the effluent. This change is captured by the conductivity detector and converted into an electrical signal, which is then analyzed and recorded by the data processing system.
[0088] The core principle of ion chromatography is to use the separation ability of ion exchange resin to separate the ions in the sample solution in order of charge number and size, and then detect the concentration of each ion through a conductivity detector.
[0089] The detection method of the present invention is as follows:
[0090] Accurately weigh a certain amount of sample from the lithium acesulfame pellets to ensure that the sample is representative.
[0091] The sample is placed in an appropriate amount of deionized water and fully stirred or ultrasonically treated to completely dissolve the lithium acesulfame particles to form a uniform solution.
[0092] The dissolved solution is filtered using an appropriate filter membrane (such as a filter membrane with a pore size of 0.45 μm or 0.22 μm) to remove insoluble impurities and particles to ensure the cleanliness of the sample solution.
[0093] Depending on the detection range of the ion chromatograph and the expected concentration of sulfate ions in the sample, the filtered solution was appropriately diluted for accurate determination.
[0094] Instrument and reagent preparation: Select an ion chromatograph equipped with an appropriate ion exchange column, conductivity detector, and data processing system. Ensure that the instrument is in good working condition and has undergone necessary calibration and verification. Prepare a mixed solution containing a certain concentration of sodium carbonate and sodium bicarbonate as the eluent. The concentration and composition of the eluent should be optimized according to the specific chromatographic column and sample characteristics. Prepare a series of sulfate ion standard solutions of known concentrations for establishing a standard curve and calibrating the instrument. The concentration range of the standard solution should cover the expected concentration of sulfate ions in the sample.
[0095] Testing steps:
[0096] 1. According to the operating manual of the ion chromatograph and the sample characteristics, set appropriate instrument parameters, such as eluent flow rate, injection volume, column temperature, etc.
[0097] 2. Inject sulfate ion standard solutions into the ion chromatograph for analysis, record the retention time and peak area of each standard solution, and draw a standard curve based on the relationship between the peak area and the concentration of the standard solution.
[0098] 3. Inject the treated lithium acesulfame particle sample solution into the ion chromatograph for analysis. Record the sample chromatogram and data, especially the retention time and peak area of sulfate ion.
[0099] 4. According to the retention time and peak area of sulfate ions in the sample, find the corresponding concentration value on the standard curve. Calculate the actual concentration of sulfate ions in the sample and perform necessary data statistics and quality control.
[0100] According to the above method, the lithium acesulfame crystals of Example 1, Comparative Example 1 and Comparative Example 2 were tested, and the results were as follows:
[0101] Example 1: The sulfate ion concentration is lower than the detection limit (lower than 0.1 mg / L), indicating that the sulfate ion content in the product is extremely low and meets the product quality requirements.
[0102] Comparative Example 1: The sulfate ion concentration is about 200 mg / L.
[0103] Comparative Example 2: The sulfate ion concentration was about 120 mg / L.
[0104] The solubility of lithium hydroxide in water is relatively low, which limits its application in certain reactions. However, by introducing sulfate ions, the present invention creates a condition that allows lithium elements to be in a dissolved state accompanied by sulfate. This strategy cleverly bypasses the obstacle of low solubility of lithium hydroxide and provides possibilities for subsequent chemical reactions. Subsequently, the present invention adopts chitosan-based sulfate adsorption materials, which have efficient and selective adsorption capacity for sulfate ions. Through protonation modification, the amino groups on the surface of the adsorption material are protonated under acidic conditions to form positively charged -NH3+, thereby adsorbing negatively charged sulfate ions through electrostatic action. This adsorption technology not only improves the removal efficiency of sulfate, but also ensures the purity of the reaction system.
[0105] The lithium acesulfame crystals prepared by the method of the present invention have the advantages of high purity, low impurity content, etc.
[0106] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing lithium acesulfame, characterized in that The following steps are involved: (a) preparing acetoacetamidosulfonate; (b) preparing a sulfur trioxide / dichloromethane solution; (c) preparing an intermediate using the products of steps (a) and (b); (d) hydrolyzing and extracting the intermediate to obtain an organic phase containing acesulfame; (e) adding lithium hydroxide to deionized water, adjusting the pH value to 6.5-7, and then reacting with the organic phase containing acesulfame; (f) removing sulfate ions from the reaction solution by adsorption using a sulfate adsorbent; (g) filtering to remove the adsorbent material, concentrating and crystallizing to obtain a crude product of lithium acesulfame; (h) washing and drying the crude lithium acesulfame.
2. The method for preparing lithium acesulfame according to claim 1, characterized in that In step (e), the pH value of the mixed solution is adjusted by adding sulfuric acid.
3. The method for preparing lithium acesulfame according to claim 1, characterized in that In step (e), the lithium ion concentration of the lithium hydroxide solution is 3-4 mol / L.
4. The method for preparing lithium acesulfame according to claim 1, characterized in that In step (f), the sulfate adsorption material is a chitosan-based sulfate adsorption material, which is prepared by a cross-linking reaction of chitosan and formaldehyde and is protonated.
5. The method for preparing lithium acesulfame according to claim 4, characterized in that In the preparation of chitosan-based sulfate adsorption material, the deacetylation degree of chitosan is between 80% and 95%, and the particle size is between 50 and 100 microns.
6. The method for preparing lithium acesulfame according to claim 4, characterized in that In the preparation of chitosan-based sulfate adsorption material, 2%-5% acetic acid solution is used as a solvent for chitosan.
7. The method for preparing lithium acesulfame according to claim 4, characterized in that In the preparation of chitosan-based sulfate adsorption material, the mass ratio of formaldehyde to chitosan is between 1:1 and 2:1, and the temperature of the cross-linking reaction is between 50-70°C.
8. The method for preparing lithium acesulfame according to claim 1, characterized in that In step (f), the adsorption operation is carried out at a temperature of 40-50° C., and the adsorption material is slowly added at a rate of 2% per minute.
9. The method for preparing lithium acesulfame according to claim 1, characterized in that In step (g), the concentration operation is carried out under the conditions of a vacuum degree of -0.08 to -0.1 MPa and a heating temperature of 60-80°C.
10. The method for preparing lithium acesulfame according to claim 1, characterized in that In step (g), when the solution reaches saturation concentration, the crystallization operation is started, and the concentration is continued until enough crude lithium acesulfame is obtained.
Citation Information
Patent Citations
Method for preparing acesulfame potassium
CN116322984A
Method for preparing acesulfamic acid through hydrolysis and production method of acesulfamic acid potassium
CN116323573A